An Arterial Spin Labeling MRI Perfusion Study of Migraine without Aura Attacks - Gil-Gouveia, Raquel; Pinto, Joana; Figueiredo, Patricia; Vilela, Pedro Ferro; Martins, Isabel Pavão (Frontiers in Neurology, 2017)
Background Studies of brain perfusion during migraine without aura attacks have inconsistent results. Methods Arterial spin labeling MRI, a non-invasive quantitative perfusion technique, was used to prospectively study a spontaneous untreated migraine without aura attack and a headache-free period. Image analysis used FSL and MATLAB software; Group analysis used permutation methods for perfusion differences between sessions. Results Thirteen women (age 35.7) were scanned during an attack of an average intensity of 6.8 (on 0–10 Visual Analog Scale) and 16 h duration. No global or regional perfusion differences were identified when comparing migraine and migraine-free sessions. Discussion Our findings suggest that the painful phase of migraine without aura attacks is not associated with brain perfusion abnormalities.